TEACHING APPRAISAL MODEL AS AN ALTERNATIVE MODEL TO IMPROVE STUDENTS’ACADEMIC WRITING COMPETENCE - Magdalena Ngongo; Eltina Maramon; Tiarma Marpaung (English Review: Journal of English Education, 2026)
This study aims to find out whether teaching appraisal model improves students’ competence in academic writing and describe the effect size for pair sample test. It was realized that students still had difficulties in using variety of appraisal features in their academic writing, including thesis writing. Therefore, this study was important to be studied in order to know whether appraisal model improved students’ competence in academic writing text. This study applied pre-experimental design to treat the students in writing academic focusing on appraisal features. The subjects of this study were 30 seventh semester students who were taking research method course or those who were in process of writing thesis as their final project. Students were treated by teaching appraisal features and asked them to identify appraisal features in text and then they were asked to use appraisal features in their own writing. Data were analyzed quantitatively by applying the paired sample t-test and omega squared. The result showed that appraisal model improved students’ competence. It was proved that the calculated value was 13.23. It was higher than the critical value table 1.70 based on the critical value table for t at α = .05. Referring to this fact, H0 was rejected because the calculated was more than critical value table; whereas H1 was accepted. The result of the effect for the paired samples t-test was 0,85, it could be interpreted this indicated about 85 % of the variance in writing self-efficacy was explained by the change from pre- test to post test. Therefore, it could only be suggested that 85% of the variance in writing self-efficacy was explained by the change from pre- test to post test. It was suggested the lecturers of academic writing, semantic, discourse analysis and research method courses could include the appraisal language as one of the topics to be discussed.